2021
DOI: 10.1108/jima-07-2021-0233
|View full text |Cite
|
Sign up to set email alerts
|

Between awareness of halal food products and awareness of halal-certified food products

Abstract: Purpose The purpose of this study are: to study the difference between halal awareness and halal certified awareness, and the relationship between the two variables; to study the differences in knowledge about halal and halal certified, as well as their relationship with halal awareness and halal certified awareness; and to build and test research models regarding factors that affect certified halal awareness. Design/methodology/approach The target population is Muslims who live in Indonesia and are 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 68 publications
(189 reference statements)
0
14
0
Order By: Relevance
“…The measurement indicators include Awareness of Halalpreneurs, Intrinsic Motivation, Obligation, Creativity, and Innovation. Usman, Chairy, and Projo (2021) showed that religious commitment has a significant role in increasing halal awareness. Religiosity and halal awareness positively affect the purchase intention of halal food (Karimah & Darwanto, 2021;Mutmainah, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement indicators include Awareness of Halalpreneurs, Intrinsic Motivation, Obligation, Creativity, and Innovation. Usman, Chairy, and Projo (2021) showed that religious commitment has a significant role in increasing halal awareness. Religiosity and halal awareness positively affect the purchase intention of halal food (Karimah & Darwanto, 2021;Mutmainah, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The system uses halal vocabulary and connects data from various sources, providing recommendations on the halal and nutritional status of a food product through web and Android applications. Usman et al (2023) examined the difference between halal awareness and halalcertified awareness among Muslim consumers in Indonesia. It also explores the relationship between knowledge about halal and halal-certified products and their impact on awareness.…”
Section: Cluster 5: Halal Food Product In Indonesiamentioning
confidence: 99%
“…Religiosity positively impacts Halal awareness and Halal food procurement decisions (Khalik & Ibrahim, Submitted for publications). Halal quality assurance system adoption could facilitate the implementation of different Halal standards (Roslan, Rahman, Hanafiah, & Abdul, 2015; Usman & Dian, 2015). Hence, the results of these two published articles can be further utilized to shape the integrated impact of different management systems including the Halal standards over organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%